Hubungan Biaya, Barriers to Entry dan Preferensi Konsumen terhadap Produktivitas UMKM di Kota Padang - Sarianja, Suherdian Septa; R, Wahyu Rahmadia; Rahayu, Witri; Clarisa, Cindy; Zefriyenni, Zefriyenni (Universitas Negeri Padang, 2025)
This study aims to determine the effect of costs, barriers to entry and consumer preferences on the Productivity of Micro, Small and Medium Enterprises (MSMEs). The unit of analysis is Micro, Small and Medium Enterprises (MSMEs) in Padang City. This study uses primary data obtained through questionnaires. The sampling technique uses quota sampling. A total of 100 questionnaires from MSMEs were returned as the final sample. The data were analyzed using multiple regression analysis conducted with SPSS software. The results showed that costs and consumer preference had a significant positive effect on productivity. While barriers to entry had a significant negative effect on productivity. MSMEs need to manage production costs more efficiently. Furthermore, MSMEs are advised to identify inefficient costs in operations and find ways to reduce them without sacrificing product quality.